2023
DOI: 10.1242/jcs.260449
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed flow increases endothelial inflammation and permeability via a Frizzled-4-β-catenin-dependent pathway

Abstract: Multidirectional or disturbed flow promotes endothelial dysfunction and is associated with early atherogenesis. Here we investigated the role of Wnt signalling in flow-mediated endothelial dysfunction. The expression of Frizzled-4 was higher in cultured human aortic endothelial cells (EC) exposed to disturbed rather than undisturbed flow, obtained using an orbital shaker. Increased expression was also detected in regions of the porcine aortic arch exposed to disturbed flow. The increased Frizzled-4 expression … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…These findings contrast with the decrease in TEER values we observed after a 2-day stimulation with Wnt7a. Of note, results similar to ours were observed in a study of human aortic ECs where similar β-catenin mediated increases in permeability were detected [ 57 ].…”
Section: Discussionsupporting
confidence: 89%
“…These findings contrast with the decrease in TEER values we observed after a 2-day stimulation with Wnt7a. Of note, results similar to ours were observed in a study of human aortic ECs where similar β-catenin mediated increases in permeability were detected [ 57 ].…”
Section: Discussionsupporting
confidence: 89%
“…37 Disruption and reduction in VE-Cadherin expression under oscillatory conditions hence suggesta possible redistribution of gap junctions and cytoskeletal proteins that can compromise the monolayer integrity and increase the membrane permeability. 42 Our data suggest that redistribution of cytoskeletal proteins due to bidirectional oscillatory flows mayalterthe membrane permeability and tractional stresses,controlled by ventral stress fibers, to change cell-substrate adhesions. A measurement of the monolayer permeability alone may not represent changes in the mechanobiological behaviors of endothelial cell monolayers.…”
Section: Ve-cadherin Disruptions Are Augmented In Monolayers Under Bi...mentioning
confidence: 69%
“…Proteomics analysis indicated that the phosphorylated fraction of β-catenin is significantly upregulated in endothelial cells that were exposed to CLL-exomes; previous studies showed that in these cells, β-catenin binds and activates NFκB [20]. In another study, Rickman et al showed that disturbed flow increases endothelial inflammation and permeability via a Frizzled-4-β-catenin-dependent pathway [34]. This is in line with our ChIP results showing that β-catenin enhances the activity of NFκB in HUVECs.…”
Section: Discussionmentioning
confidence: 97%